2017
DOI: 10.1002/tox.22525
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low‐dose melamine exposure during pregnancy on maternal and fetal kidneys in rats

Abstract: Despite the previous reports on melamine contamination in high concentrations some years ago, there were not many studies on low-level exposure in daily life, particularly in pregnancy. We investigated the effect of low-dose melamine on the kidneys of the pregnant rats and their developing embryos/fetuses during various gestational stages namely implantation, gastrulation, organogenesis, maturation and whole pregnancy. Our results showed that the repeated low level of melamine (12.5, 25, and 50 mg/kg bw/d) dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
(121 reference statements)
1
10
0
Order By: Relevance
“…Previous studies confirmed that melamine can change the structure of the kidney and induce kidney disease 38,41 . It was indicated that melamine could induce renal toxicity in pregnant rats 42 . In this study, pathophysiological changes of kidney was also induced by melamine.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies confirmed that melamine can change the structure of the kidney and induce kidney disease 38,41 . It was indicated that melamine could induce renal toxicity in pregnant rats 42 . In this study, pathophysiological changes of kidney was also induced by melamine.…”
Section: Discussionsupporting
confidence: 65%
“…Given that the nephrotoxic effects of melamine are mediated by uric acid, probably not cyanuric acid, its potential risk to human health may be low. However, recent epidemiological studies suggested that the pathogenic mechanisms are different between low chronic and acute exposure (e.g., 2008 Chinese melamine-tainted food scandal) of melamine , and that the low and continuous melamine exposure was linked to the risk of uric acid and calcium urolithiasis. Furthermore, the TDI value reported above was derived from a short-term animal toxicity assay conducted 30 years ago . More stringent regulations on melamine in food are needed, especially considering the synergistic effects of melamine with other environmental chemicals, including cyanuric acid, , uric acid, and di­(2-ethylhexyl) phthalate .…”
Section: Resultsmentioning
confidence: 99%
“…6,14,17,18 No human studies have attempted to examine the effect of maternal melamine exposure on kidney function or renal morphology in their fetuses; only animal studies have investigated this relationship. [21][22][23][24][25][26][27][28][29] Our use of isotope dilution liquid chromatography/tandem mass spectrometry (LC/MS/MS), which we plan to use in the second stage of our studies, has found melamine in the placenta of humans.…”
Section: Siaogang Hospitalmentioning
confidence: 99%
“…In mammals, mother and fetal compartments are separated by the placenta, an organ that connects the developing fetus to the uterine wall and the only source of nutrients from the pregnant mother . Animal studies, which have detected melamine in the placentas, amniotic fluid, and even fetus or neonatal kidney in rats, have concluded that melamine can cross the placental barrier and enter the fetus …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation